The Canticle of the creatures and sustainability: Listening to the cry of the Earth - Martín Carbajo-Núñez (Warszawskie Studia Teologiczne)
Recognizing that “everything is interconnected,” this article explores the ecological challenges posed by the current economic system, which prioritizes material growth and fuels relentless consumerism. Rather than addresing genuine human needs—which are naturally limited—it stimulates unlimited desires, endangering the sustainability of the global ecosystem and amplifying the cry of the earth (Part 1). The Human being is portrayed as an insatiable consumer, locked in constant conflict with the world around him (Part 2). To overcome this cycle of struggle and self-destruction, we must foster a new relational paradigm inspired by Francis of Assisi and his Canticle of the Creatures (Part 3).